Hubungan Interaksi Teman Sebaya dan Akses Media Sosial dengan Tingkat FoMO pada Remaja - Riyani lintang Viona; Nanang Martono; Amalia Nur Ramadhani (The Journal of Society and Media, 2026)
Fear of Missing Out (FoMO) has emerged as a growing phenomenon that influences adolescents’ psychological well-being and social behavior. FoMO reflects a perceived gap between direct social interactions with peers and indirect engagement through social media, often leading to anxiety and dissatisfaction with one’s life. This study aims to examine the relationship between peer interaction, social media access, and FoMO levels among adolescents. A survey method was employed, and the research was conducted at a senior high school in Purwokerto involving 210 students. Data were collected through questionnaires and interviews. The findings indicate a positive relationship between peer interaction and FoMO, with a significance value of 0.000 (p < 0.05) and a product-moment correlation coefficient of 0.41, suggesting a low association. Social media access also shows a positive relationship with FoMO (p = 0.003 < 0.05), with a correlation coefficient of 0.28, indicating a weak relationship. Regression analysis reveals a constant of 1.479, with regression coefficients of 0.41 for peer interaction and 0.31 for social media access, demonstrating that peer interaction has the more dominant influence. Overall, peer interaction and social media access are weakly associated with FoMO levels, indicating that adolescents’ engagement with peers and social media does not necessarily increase anxiety